A Study on Formative Assessment of EFL in the Multimedia-based Environment in China - Hui, Han; Wei, Wang (Asian Journal of Assessment in Teaching and Learning, 2013)
An effective assessment system is indispensable to the current reform of EFL teaching in China which emphasizes the importance of the Multimedia Computer-assisted Language Learning (MCALL). A tentative model of formative assessment for MCALL is designed and implemented in two classes attended by 58 students. Qualitative and quantitative data show that the introduced assessment system not only stimulates learner’s motivation and interest to learn, but also makes it possible to monitor and facilitate learner’s learning process as well as their autonomy in learning. More noticeably observed is the successfully cultivation of learner’s autonomy, cooperative learning and communicative skills.